IMPLEMENTATION OF VARIED SMOKING METHODS IN THE PROCESS OF KATSUOBUSHI (WOODY SMOKED FISH) SKIPJACK (Katsuowonus pelamis) - Meldiyani Br karo; Sukirno Mus; Tjipto Leksono (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The aim of the research was to determine the effectiveness of smoking method implemented forproducing katsuobushi (woody smoked fish). The processes were distinguished into two methods, namely: liquid smoking (Pc) and traditional smoking (Pt). Skipjack katsuobushi produced were then evaluated for their quality, including: the value of organoleptic, the value of pH, the content of moisture, acids, and phenols. The results showed that the quality of the katsuobushi produced by implementing the liquid smoking method was significantly different from that produced by implementing traditional smoking one. The value of the odor, flavor, and the content of moisture, phenols and acids, katsuobushi skipjack produced by liquid smoking methods were higher, whilst the value of colour and pH were lower and significantly different than those produced by implementing traditional smoking. Both kinds of katsuobushi skipjack were overgrown by fungi Aspergillus sp. and Penicillum sp. indifferent intensities. The growth intensity of the fungi on the surface of katsuobushi skipjack produced by implementing traditional smoking was higher than that produced by implementing liquidsmoking.Keywords: katsuobushi, liquid smoking,skipjack, traditional_________________